Adipokines as Possible New Predictors of Cardiovascular Diseases: A Case Control Study - Laura Pala; Matteo Monami; Silvia Ciani; Ilaria Dicembrini; Alessandro Pasqua; Anna Pezzatini; Paolo Francesconi; Barbara Cresci; Edoardo Mannucci; Carlo Maria Rotella (Journal of Nutrition and Metabolism)
Background and Aims. The secretion of several adipocytokines, such as adiponectin, retinol-binding protein 4 (RBP4), adipocyte fatty acid binding protein (aFABP), and visfatin, is altered in subjects with abdominal adiposity; these endocrine alterations could contribute to increased cardiovascular risk. The aim of the study was to assess the relationship among adiponectin, RBP4, aFABP, and visfatin, and incident cardiovascular disease. Methods and Results. A case-control study, nested within a prospective cohort, on 2945 subjects enrolled for a diabetes screening program was performed. We studied 18 patients with incident fatal or nonfatal IHD (Ischemic Heart Disease) or CVD (Cerebrovascular Disease), compared with 18 matched control subjects. Circulating adiponectin levels were significantly lower in cases of IHD with respect to controls. Circulating RBP4 levels were significantly increased in CVD and decreased in IHD with respect to controls. Circulating aFABP4 levels were significantly increased in CVD, while no difference was associated with IHD. Circulating visfatin levels were significantly lower in cases of both CVD and IHD with respect to controls, while no difference was associated with CVD. Conclusions. The present study confirms that low adiponectin is associated with increased incidents of IHD, but not CVD, and suggests, for the first time, a major effect of visfatin, aFABP, and RBP4 in the development of cardiovascular disease.